2020
DOI: 10.2147/ndt.s254369
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cognitive Impairments in Early-Detoxified Alcohol-Dependent Inpatients and Their Associations with Socio-Demographic, Clinical and Psychological Factors: An Exploratory Study</p>

Abstract: Cognitive impairment is common among patients with alcohol use disorder (AUD). However, neuropsychological assessment is not usually included as routine practice in alcohol rehabilitation programs. The aim of this study was to describe qualitatively the cognitive deficits in early-detoxified AUD patients undergoing rehabilitation and to explore relevant associations with socio-demographic, clinical and psychological factors. Patients and Methods: Forty-one patients with a diagnosis of AUD were consecutively re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 75 publications
2
15
0
Order By: Relevance
“…The cognitive impairments affected predominantly visuospatial abilities, executive functions and memory. Our results are in line with several studies that have demonstrated impaired performance on visuospatial processing, executive functions and episodic memory in AUD subjects ( 6 , 10 , 45 ). The 80.5% of the total sample showed impaired performance on at least one subscale of the neuropsychological battery.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The cognitive impairments affected predominantly visuospatial abilities, executive functions and memory. Our results are in line with several studies that have demonstrated impaired performance on visuospatial processing, executive functions and episodic memory in AUD subjects ( 6 , 10 , 45 ). The 80.5% of the total sample showed impaired performance on at least one subscale of the neuropsychological battery.…”
Section: Discussionsupporting
confidence: 93%
“…Although the maintenance of sobriety is associated with cognitive recovery, some deficits may persist and interfere with the motivation process of patients to change their addictive behavior (4). The literature showed that after alcohol detoxification, 50-80% of the recently abstinent subjects present neuropsychological impairments (5)(6)(7). Alcohol-related brain damage is characterized by a brain volume deficit, a dilatation of the ventricles and an increased cerebrospinal fluid quantity, involving several brain regions: cerebellum, corpus callosum, hippocampus, thalamus, amygdala, and frontal cortices (8).…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Interestingly, although the relationships between HPA axis activity, craving and behavioural performance during early abstinence have been documented, little is known on such a relationship during protracted abstinence. [19][20][21][22] The early abstinence period is associated with a decrease in plasmatic GCs concentration, as opposed to a brain regional GCs increase, particularly in the PFC, likely involving genomic effects of GCs. 23 Hence, it seems that the transition from positive to negative reinforcement in alcohol dependence is driven by a dysregulated HPA axis function, in which the role of GRs and GCs remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and experimental studies in both humans and rodents have shown that both acute and chronic alcohol consumption, as well as alcohol withdrawal, enhanced plasma glucocorticoids (GCs) and decreased GCs receptors’ (GR) availability [17, 18]. Interestingly, although the relationships between HPA axis activity, craving, and behavioural performance during early abstinence have been documented, little is known on such a relationship during protracted abstinence [19, 20, 21, 22]. The early abstinence period is associated with a decrease in plasmatic GCs concentration, as opposed to a brain regional GCs increase, particularly in the PFC, likely involving genomic effects of GCs [23].…”
Section: Introductionmentioning
confidence: 99%